Prevalence of Pulmonary Tuberculosis in Jutpani VDC, Chitwan, Nepal - Amgain, Kapil; Maharjan, Mahendra (Nepalese Journal of Zoology, 2015)
Tuberculosis (TB) is one of the major public health problems in the developing countries like Nepal. The present study was carried out in Jutpani VDC of Chitwan Nepal from July to December 2012 with the objective to determine the situation of Tuberculosis in Jutpani VDC, Chitwan. During the study period, a total of 600 sputum samples from 200 TB suspected patients were collected and examined in the Laboratory of Jutpani Primary Health Center (PHC). Diagnosis was made after staining the sputum smear by Z-N staining method and examined under light microscope. Out of 200 TB suspected patients, 18(9%) were found to be AFB positive. Among patients diagnosed as having pulmonary Tuberculosis (PTB), males (55.56%) were found to be infected more than females (44.44%) which was found to be statistically insignificant (Χ2cal. = 0.4524, P<0.01). Highest prevalence of TB infection (36.89%) was found to be in the age group of 30-40 years. A questionnaire survey of 57 Pulmonary Tuberculosis (PTB) patients was done to assess their knowledge, attitude and preventive practices for TB. Out of 57 PTB patients interviewed, majority of the patients had positive attitude but the knowledge regarding cause, transmission, prevention of the tuberculosis was not adequate.